20(S)-protopanaxadiol prolongs lifespan and enhances stress resistance in Caenorhabditis elegans via the insulin/IGF-1 signaling pathway - Song, Zhuo; Yan, Xiuci; Xu, Xiaohao; Lou, Tingting; Wang, Yu; Ren, Limei; Liu, Fangbing; Zhang, Shuai (Frontiers in Pharmacology, 2025)
IntroductionAging is a progressive and irreversible process linked to a variety of diseases. Examination of the processes targeted by pharmacological treatments could potentially both extend lifespan and alleviate age-associated diseases. 20(S)-protopanaxadiol (20(S)-PPD), a primary ginsenoside metabolite, has many beneficial properties, although it`s anti-aging effects are unknown.MethodsLifespan and behavioral assays were used to determine the effects of 20(S)-PPD on life span and healthy lifespan. Stress resistance was systematically determined under heat, oxidative, and chemical stress conditions. The target of 20(S)-PPD was identified by molecular docking and surface plasmon resonance. Investigation in mutant worms identified the signaling pathway and transcription factor mediating 20(S)-PPD-induced longevity.Results20(S)-PPD could significantly extend Caenorhabditis elegans (C. elegans) lifespan without affecting food intake and reproductive output. It also improved healthspan in aging worms by ameliorating locomotor deficits and suppressing lipofuscin accumulation. Furthermore, 20(S)-PPD enhanced stress resistance and reduced age-associated reactive oxygen species (ROS) levels. Mechanistically, 20(S)-PPD bound dose-dependently to the insulin receptor (IR) with a KD value of 8.59 μM. The life-extending effects of 20(S)-PPD involved the DAF-2/insulin/IGF-1 signaling (IIS) pathway, rather than other conserved pathways. Treatment with 20(S)-PPD promoted DAF-16/FOXO activation and nuclear translocation, leading to upregulated transcription of several antioxidant and detoxification-related genes, including lys-7, mtl-1, hsp-12.6, dod-3, sod-3, hsp-16.2, gst-4 and sms-1. 20(S)-PPD also upregulated the protein levels of SOD-3 and GST-4, known promoters of longevity in C. elegans.ConclusionThese findings demonstrate that IR is a molecular target of 20(S)-PPD and reveal a mechanism by which 20(S)-PPD promotes longevity and stress resistance, suggesting the potential of 20(S)-PPD in slowing aging and the development of age-associated disorders.